2018
DOI: 10.1590/0001-3765201820170967
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Microtetrameres (Nematoda, Tetrameridae) parasitizing Buteogallus urubitinga (Aves, Accipitridae) from northeastern Argentina

Abstract: A new tetramerid nematode, Microtetrameres urubitinga n. sp., is described from specimens recovered from the proventriculus of the great black-hawk, Buteogallus urubitinga (Aves: Accipitridae), from Formosa Province, Argentina. The males of the new species are characterized by having spicules unequal (length ratio of spicules 1:3.8-5.9) and dissimilar in shape (right spicule with a simple tip, left spicule with a symmetrical bifurcated tip), caudal papillae arranged asymmetrically (two pairs precloacal and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…However, males are generally found on the mucosa or in the lumen of the proventriculus moving freely between the crypts and the lumen. This finding confirms the previous suggestion that the males move nearby spontaneously to reach and fertilize the immobile females [18,26] . The living females of M. spiralis that were collected from the epithelial lining of the proventricular glands in adjacent connection with their anterior ends have a red colour.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, males are generally found on the mucosa or in the lumen of the proventriculus moving freely between the crypts and the lumen. This finding confirms the previous suggestion that the males move nearby spontaneously to reach and fertilize the immobile females [18,26] . The living females of M. spiralis that were collected from the epithelial lining of the proventricular glands in adjacent connection with their anterior ends have a red colour.…”
Section: Discussionsupporting
confidence: 92%
“…Both subgenera Tetrameres and Microtetrameres were raised to generic category based on female body form; globular or spindle-shaped in Tetrameres and with its longitudinal axis spirally coiled in Microtetrameres [15] . The genus Microtetrameres currently includes several species parasitic in birds worldwide [1,3,[16][17][18][19] . In the agricultural country like Egypt; man is usually in close interaction with water, therefore there is a potential danger of invasion with nematodes of birds.…”
Section: Introductionmentioning
confidence: 99%
“…Physaloptera acuticauda Molin, 1860 and Physaloptera inflata Molin, 1860 have been recorded in P. unicinctus from South America (Cram, 1927;Yamaguti, 1961). Microtetrameres (Travassos, 1915) inhabits the proventriculus of birds, with females strictly associated with proventricular glands and males with the proventricular mucosa (Anderson, 2000;Díaz et al, 2018). Members of the family Tetrameridae have an indirect life cycle, with arthropods such as grasshoppers and cockroaches serving as intermediate hosts (Anderson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In South America, there are few records for this genus, with most of them coming from passerine birds and only one record from a bird of prey. Díaz et al (2018) recently reported a new species for the Neotropics, Microtetrameres urubitinga Díaz, Drago & Núñez, 2018, parasitizing the proventriculus of Buteogallus urubitinga (Gmelin, 1788) in Argentina. The present Microtetrameres sp.…”
Section: Discussionmentioning
confidence: 99%
“…SI: proventriculus, females within the glands and males free in the lumen. DueñasDíaz et al (2018). Bernal(-34.6956, -58.2667), Buenos Aires Province.…”
mentioning
confidence: 99%